Searching for indole derivatives as potential mushroom tyrosinase inhibitors. (3rd May 2016) - Ferro, Stefania; Certo, Giovanna; De Luca, Laura; Germanò, Maria Paola; Rapisarda, Antonio; Gitto, Rosaria
Abstract: Tyrosinase is a copper-containing enzyme widely distributed in nature, involved in the biosynthesis of melanin whose role is to protect the skin from ultraviolet damage. A great interest has been shown on the melanin involvement in malignant melanoma and other carcinogenetic processes. These phenomena have encouraged the research of tyrosinase inhibitors useful in therapeutic field as well as in foods and cosmetics to prevent browning. The idea was to screen our " in house " database to select suitable lead compounds for the discovery of potential drug-inhibiting enzyme. The obtained biological results demonstrated that compounds containing 4-fluorobenzyl moiety at N − 1 position of indole system showed the best activity. In addition, the role of the portion linked to the carbonyl group at C − 3 was discussed. A Lineweaver–Burk kinetic analysis of the most active indoles, CHI 1043 and derivative4, showed a mixed-type inhibition in the presence ofl -3, 4-dihydroxyphenylalanine (l -DOPA) as substrate.